COMPUTER INTEGRATED MANUFACTURING (CIM) SYSTEM: STRATEGI SISTEM MANUFAKTUR UNTUK MENINGKATKAN KUALITAS PRODUKSI - Sabihaini Sabihaini (Akutansi Bisnis & Manajemen ( ABM ), 2002)
The popular press often writes about the factory of the future: a fully automated factory that manufactures a wide variety of products without human intervention. Although some peopless factories do exits and others will be built, the major advances being made today occur in manufacturing operations where computers are being integrated into the process to help workers create high quality products. Computer Integrated Manufacturing (CIM) is an umbrella term for the total integration of product design and engineering, process planning, and manufacturing by means of complex computer systems. Less comprehensive computerized systems for production planning, inventory control, or scheduling are often considered part of CIM. By using this powerful computer systems to integrated all phases of manufacturing, from initial customer order to final shipment, firms hope to increase productivity, improve quality, meet customer needs faster, and offer more flexibility.